Pressure-induced Lifshitz and structural transitions in NbAs and TaAs: experiments and theory. (11th April 2018) - Gupta, Satyendra Nath; Singh, Anjali; Pal, Koushik; Muthu, D V S; Shekhar, C; Elghazali, Moaz A; Naumov, Pavel G; Medvedev, Sergey A; Felser, C; Waghmare, U V; Sood, A K
Abstract: High pressure Raman, resistivity and synchrotron x-ray diffraction studies on Weyl semimetals NbAs and TaAs have been carried out along with density functional theoretical (DFT) analysis to explain pressure induced structural and electronic topological phase transitions. The frequencies of first order Raman modes harden with increasing pressure, exhibiting a slope change at GPa for NbAs and GPa for TaAs. The resistivities of NbAs and TaAs exhibit a minimum at pressures close to these transition pressures and also a change in the bulk modulus is observed. Our first-principles calculations reveal that the transition is associated with an electronic Lifshitz transition at for NbAs while it is a structural phase transition from body centered tetragonal to hexagonal phase at for TaAs. Further, our DFT calculations show a structural phase transition at 24 GPa from body centered tetragonal phase to hexagonal phase.